Design and Development Frequency Sensing System for Real-Time Elephant Tracking - Che Jemani, Che Muhammad Umair Aiman; Alias, Afishah (Enhanced Knowledge in Sciences and Technology, 2025)
Human-wildlife conflict, particularly involving elephants, presents significant challenges to both conservation efforts and human livelihoods. This study addresses these issues by designing an animal detection and deterrence system. The system integrates ultrasonic, motion, and thermal sensors with a NodeMCU-ESP32 microcontroller to monitor and deter wildlife from entering designated buffer zones. The system leverages sensor data to identify animal presence through movement, proximity, and heat signatures. The microcontroller processes these inputs using predefined thresholds, ensuring accurate detection while minimizing false positives. Upon validation of animal presence, an alarm system is triggered to deter the intruder. Experimental results demonstrate the system’s reliability, with stable operation in normal conditions and effective detection of animals, as indicated by variations in sensor data. This system offers a cost-effective and scalable solution for mitigating human-wildlife conflicts, ensuring safety for both humans and wildlife.